2019
DOI: 10.15244/pjoes/92812
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution and Pollution Assessment of Potentially Toxic Elements in Urban Forest Soil of Nanjing, China

Abstract: With rapid development of industrialization and urbanization, potentially toxic elements (PTEs) contamination has become a popular problems in China. Many researchers have studied the effects of PTE contamination in agricultural soils [1-2]. Some elements are necessary or beneficial to plants at certain levels, such as Cu, Zn, and Ni. Fertilization with Zn improves water use efficiency, grain yield, and content of seed Zn in chickpea [3], and the experiments conducted at a total of 23 experimental site-years i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Therefore, it is crucial to obtain a comprehensive understanding of the content and distribution of heavy metals in the soil [14,15]. Although China's exploration into heavy metals in urban soil commenced relatively recently, contemporary scholars have diligently investigated the content, distribution, and sources of soil heavy metal pollution in numerous large-and medium-sized cities, including Haikou, Beijing, Nanjing, and Shanghai [16][17][18][19][20][21][22][23]. The single factor index method was employed to assess the heavy metal pollution of the soil near the river, revealing severe pollution in the area, particularly from Cd [24].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is crucial to obtain a comprehensive understanding of the content and distribution of heavy metals in the soil [14,15]. Although China's exploration into heavy metals in urban soil commenced relatively recently, contemporary scholars have diligently investigated the content, distribution, and sources of soil heavy metal pollution in numerous large-and medium-sized cities, including Haikou, Beijing, Nanjing, and Shanghai [16][17][18][19][20][21][22][23]. The single factor index method was employed to assess the heavy metal pollution of the soil near the river, revealing severe pollution in the area, particularly from Cd [24].…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these shortcomings, various mathematical theories such as the fuzzy mathematic method [4,[14][15][16], analytic hierarchy process [17,18], grey theory method [19], and extension method [20] have been presented to specify the pollution grade of samples based on measured values of some pollution indicators. These methods have made some achievements in evaluating soil heavy metal pollution, but they have some limitations in their processes.…”
Section: Introductionmentioning
confidence: 99%
“…Much research has reported the sediment quality status of lakes, rivers, reservoirs and groundwater in China, such as the freshwater Poyang Lake [12], eutrophic plateau Erhai Lake [11], Taihu Lake [13,14], deep mountain Sayram Lake [15], the reservoirs of Tongjiqiao Reservoir [16], Three Gorges Reservoir [17] and groundwater [18,19] they were all contaminated with heavy metals to varying degrees, anthropogenic contaminate having become a serious public environmental problem in some lakes. With the rapid developing industrial operations and fast urban expansion since 1970s, soil, water and sediment polluted by heavy metals has been both serious and widespread in many provinces [20][21][22]. For the past few years, researchers have studied the contaminate status of trace elements in arid soil [23], water [24] and sediments [25], as well as ecological heavy metal risks.…”
Section: Introductionmentioning
confidence: 99%